2005
DOI: 10.1002/ts.14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in nutritive and anti‐nutritive contents of African yam bean (Sphenostylis stenocarpa)

Abstract: Seeds of 20 African yam bean collections were evaluated for nutritive and anti‐nutritive contents. Anti‐nutrients were negatively correlated with protein and carbohydrate contents. Principal component analysis and the Fastclus procedure showed that collections with high anti‐nutrient contents had darker seed colour. Copyright © 2005 John Wiley & Sons, Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…They may be attributed to polyphenols or tannin-like compounds. Some workers (Asuzu and Undie, 1986;Okeola and Machuka, 2001;Ajibade et al, 2005) have identified the presence of some antinutritional factors (ANF) such as alkaloids, flavonoids, saponins, lectin, trypsin inhibitors, phytate and oxalate in the African yam. List of the anti-nutritional factors in the African yam bean includes trypsin inhibitor, haemagglutinating, tannic acid (tannins), phytic acid, oxalate (Apata and Ologhobo, 1997).…”
Section: Anti-nutritionals Factors Content Of Yam Chipsmentioning
confidence: 99%
“…They may be attributed to polyphenols or tannin-like compounds. Some workers (Asuzu and Undie, 1986;Okeola and Machuka, 2001;Ajibade et al, 2005) have identified the presence of some antinutritional factors (ANF) such as alkaloids, flavonoids, saponins, lectin, trypsin inhibitors, phytate and oxalate in the African yam. List of the anti-nutritional factors in the African yam bean includes trypsin inhibitor, haemagglutinating, tannic acid (tannins), phytic acid, oxalate (Apata and Ologhobo, 1997).…”
Section: Anti-nutritionals Factors Content Of Yam Chipsmentioning
confidence: 99%
“…Research has been carried out on AYB concerning morphological characteristics of the crop (Akande, 2009;Popoola et al, 2011); genetic variability in its seed quality (Olasoji et al, 2011); nutritive and antinutritive factors in the beans (Ajibade et al, 2005). However, there is little baseline information on the relationships between seed yield, tuber production and their components coupled with its improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Olasoji et al (2011) reported genetic variability in its seed quality; Akande (2009) and Popoola et al (2011) reported on the morphological characteristics of the crop. Ajibade et al (2005) reported on the nutritive and anti-nutritive factors in African yam bean while Uguru and Madukaife (2001) reported the protein content.…”
Section: Introductionmentioning
confidence: 99%